Fabrication of ABS/Graphene Oxide Composite Filament for Fused Filament Fabrication (FFF) 3D Printing - C. Aumnate; A. Pongwisuthiruchte; P. Pattananuwat; P. Potiyaraj (Advances in Materials Science and Engineering)
Additive manufacturing, the so-called three-dimensional (3D) printing, is a revolutionary emerging technology. Fused filament fabrication (FFF) is the most used 3D printing technology in which the melted filament is extruded through the nozzle and builds up layer by layer onto the build platform. The layers are then fused together and solidified into final parts. Graphene-based materials have been positively incorporated into polymers for innovative applications, such as for the mechanical, thermal, and electrical enhancement. However, to reach optimum properties, the graphene fillers are necessary to be well dispersed in polymers matrix. This study aims to emphasise the interest of producing ABS/graphene oxide (GO) composites for 3D printing application. The ABS/GO composite filaments were produced using dry mixing and solvent mixing methods before further melt extruded to investigate the proper way to disperse GO into ABS matrix. The ABS/GO composite filament with 2 wt.% of GO, prepared from the solvent mixing method, was successfully printed into a 3D model. By adding GO, the tensile strength and Young’s modulus of ABS can be enhanced. However, the ABS/GO composite filament that was prepared via the dry mixing method failed to print. This could be attributed to the aggregation of GO, leading to the die clogging and failure of the printing process.